Applying labour law to micro, small and medium-sized enterprises: A comparative study of 16 countries - Ana María Vargas (International Labour Organization (ILO), 2020)
The self-employed and micro, small and medium-sized enterprises (MSMEs) account for the greatest share of employment and make up the largest number of economic units worldwide. However, some countries exclude these economic units from certain obligations under their national labour laws in the belief that such obligations may impair enterprise growth and prosperity. This study considers the ways in which different countries regulate labour rights for MSME workers, its main purpose being to improve understanding of current trends and developments in this area. The 16 countries covered by the study are Brazil, China, Colombia, Costa Rica, Egypt, Germany, Mexico, Nepal, Peru, the Russian Federation, South Africa, Spain, Sri Lanka, Sweden, Turkey and the United Republic of Tanzania. Drawing on comparative analysis of labour law coverage for MSMEs in the above countries, this study identifies a general trend towards the extension of equal protection to all workers regardless of the enterprise size, including those in the informal economy and in self-employment. To achieve that, governments are relying not only on labour laws but also on other frameworks and policies. This study did not find any country that completely excluded MSMEs from the application of labour laws. Where selective exclusions or special regimes are in place, these apply mainly to micro and small enterprises, while workers in medium-sized enterprises are often fully covered. Invoking the concept of "social control", this study highlights a number of innovative approaches used to achieve enforcement of, and compliance with, labour laws among MSMEs - ranging from targeted inspections to wider campaigns designed to raise awareness and change social norms and perceptions. On the whole, the findings presented in this working paper tie in with those of other studies, showing how labour legislation as such is neither a major obstacle nor a panacea when it comes to promoting enterprise growth and sustainability. It would be worth undertaking further research to explore the ways in which recent labour law reforms in a number of countries have had an impact on the day-today experience of MSME workers.
Keywords: 330; informal employment; labour law; microenterprises; small enterprises; informal economy; labour administration; labour inspection